The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1007/s11183-005-0094-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional Identification of H+-ATPase and Na+/H+ Antiporter in the Plasma Membrane Isolated from the Root Cells of Salt-Accumulating Halophyte Suaeda altissima

Abstract: A membrane fraction enriched in plasma membrane (PM) vesicles was isolated from the root cells of a salt-accumulating halophyte Suaeda altissima (L.) Pall. by means of centrifugation in discontinuous sucrose density gradient. The PM vesicles were capable of generating ∆ pH at their membrane and the transmembrane electric potential difference ( ∆ψ ). These quantities were measured with optical probes, acridine orange and oxonol VI, sensitive to ∆ pH and ∆ψ , respectively. The ATP-dependent generation of ∆ pH wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Our experiments with S. altissima [13,17] showed that Na + accumulation in the root xylem of euhalophytes is accomplished by the Na + /H + antiporter located at the plasma membrane of parenchymal cells adjacent to the xylem. BALNOKIN et al . The diversity of morphological and anatomical traits in halophytes (e.g., the presence or absence of salt glands in leaves, occurrence of xeromorphic or succulent-type tissue structures) raises the question of possible differences in organization of ion transport and water relations in various halophytes.…”
Section: Introductionmentioning
confidence: 76%
“…Our experiments with S. altissima [13,17] showed that Na + accumulation in the root xylem of euhalophytes is accomplished by the Na + /H + antiporter located at the plasma membrane of parenchymal cells adjacent to the xylem. BALNOKIN et al . The diversity of morphological and anatomical traits in halophytes (e.g., the presence or absence of salt glands in leaves, occurrence of xeromorphic or succulent-type tissue structures) raises the question of possible differences in organization of ion transport and water relations in various halophytes.…”
Section: Introductionmentioning
confidence: 76%
“…Secondly, xylem Na + loading may be a thermodynamically active process that requires energy to pump Na + into the xylem (De Boer and Volkov, 2003;Lun'kov et al, 2005;Shabala and Mackay, 2011). Indeed, given the highly negative membrane potential values for halophyte parenchyma cells (e.g.…”
Section: Targeting Xylem Ion Loadingmentioning
confidence: 99%
“…The underlying transport mechanisms involved in both Na + loading into the xylem and its retrieval from the transpiration stream also remain highly controversial. Both passive (Wegner and Raschke, 1994; Wegner and De Boer, 1997; Köhler and Raschke, 2000) and active (De Boer and Volkov, 2003; Lun’kov et al. , 2005; Munns and Tester, 2008) models have been vigorously advocated.…”
Section: Introductionmentioning
confidence: 99%